Resident gut microbiota community determines the efficacy of soluble fiber in reducing adiposity - Shallangwa, Swang M.; Ross, Alexander W.; Walker, Alan W.; Morgan, Peter J. (Frontiers in Microbiology, 2024)
Consumption of dietary fiber has been linked to several health benefits. Among these, dietary fiber breakdown through the process of anaerobic fermentation by the colonic microbiota leads to the production of beneficial metabolites, mainly short-chain fatty acids (acetate, propionate, and butyrate), which have been implicated in reduced calorie intake. Nevertheless, the link between gut microbiota and obesity remains unclear. We investigated the effects of dietary fibers on food intake and body weight gain in two independent but similarly designed studies in rats. In the first study, the inclusion of 10% w/w pectin, fructooligosaccharides or beta-glucan (n=10/group) in the diets each significantly reduced body weight gain ('responders') compared to the cellulose control whereas, in a closely matched, but not fully identical study (n=8/group), no effect of dietary fiber on body weight ('non-responders') was observed. The aim of this work was to explore the basis of this differential response between the two similarly designed and comparable studies, with a focus on the potential role of the gut microbiota in the control of food intake and body weight.